2022
DOI: 10.9734/ijpss/2022/v34i2231542
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Panchgavya and Jeevamrit on Growth, Yield and Quality of Tomato (Solanum lycopersicum L.)

Abstract: The experiment was conducted on “Influence Of Panchgavya And Jeevamrit On Growth, Yield And Quality Of Tomato (Solanum Lycopersicum L.)” during the period of October 2021 to March 2022 at Horticulture Research Farm, Department of Horticulture, Naini Agricultural Institute, Sam Higginbottom, University of Agriculture, Technology and Sciences, Prayagraj (Uttar Pradesh). The experiment was planned in a factorial randomized block design (FRBD) with three replications and nine treatments which comprised of T0-(RDF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The pull-down analyses and LCI tests confirmed that nSlSPX1 and nSlSPX4 interact with cSlPHL1 (Figure 10). Thus, our differing results from Singh et al (2023) are most likely due to distinct experimental designs. Likewise, it is the C-terminus of OsPHR2 that is capable of binding to OsSPX1, OsSPX2, SPX4, and SPX6 (Lv et al, 2014;Wang et al, 2014b;Zhong et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The pull-down analyses and LCI tests confirmed that nSlSPX1 and nSlSPX4 interact with cSlPHL1 (Figure 10). Thus, our differing results from Singh et al (2023) are most likely due to distinct experimental designs. Likewise, it is the C-terminus of OsPHR2 that is capable of binding to OsSPX1, OsSPX2, SPX4, and SPX6 (Lv et al, 2014;Wang et al, 2014b;Zhong et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, silencing of SlSPX1 enhanced the transcript levels of SlPAP10b and SlPAP15 as well as the APase activity (Figure 11). Also, silencing of SlSPX1 was found to promote plant growth and root mycorrhization in tomato (Singh et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations